Reinforcement of Judicial Supervision Function by Judicial Commission and Supreme Court as a Form of Shared Responsibility System - A Antikowati; Mardi Handono (Sociological Jurisprudence Journal, 2018)
The function of judicial power is to enforce law and justice in the framework of protecting society through justice system based on law in a democratic state of law. One of the important principles of state of law is the existing guarantee of judicial power implementation which is independent, free from the influence of other power to implement justice for law and justice enforcement. Accountability of judge’s performance and Supreme Court institution which is a control form for justice institution becomes an idea concerning the dilema of judicial power independence concept. The supervision of judge’s behaviour by Judicial Commission can hopefully cover the weakness intern supervision by Supreme Court. The judge supervision which can be realised by Judicial Commission includes judicial technic supervision, performance assessment, and judge’s behaviour supervision. This research concerned to the reinforcement of judicial supervision function by judicial commission and Supreme Court as a form of shared responsibility system. The research method used in this research is normative law research method with statute approach, conceptual approach and case approach. Sources of legal materials used are legislation and cases. The results of this study are: the supervision on the judge’s behavior by the Judicial Commission can hopefully cover the weakness of internal supervision by the Supreme Court. It becomes so appropriate that the suprevision on judge is also performed by the Judicial Commission, not only by the Supreme Court. The supervision on judge that can be performed by the Judicial Commission includes the suprevision of judicial technique, performance assessment, and supervision on the judge’s behavior.